2001
DOI: 10.1159/000046108
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Dietary Calcium Restriction: A Diagnostic Approach in Idiopathic Hypercalciuria

Abstract: Background: Although frequently observed, the etiology of idiopathic hypercalciuria (IHC) remains largely unknown. A common hypothesis postulates intestinal hyperabsorption and/or a primary renal leak as the pathophysiological basis. The aim of our study was to investigate the regulation pattern of calcium homeostasis in patients with IHC by using a prolonged period of calcium restriction. Methods: Twenty-seven patients with IHC were investigated. After a 3-week run-in period (dietary calcium content 700–1,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…22 Recent trials have focused on differentiating subtypes of idiopathic hypercalciuria using prolonged dietary calcium restriction (300 mg/24 h for 3 weeks, 700-1000 mg/24 h for 4 weeks); this revealed that one subset of subjects responded to a low-calcium diet with increasing urinary calcium loss and compensatory rise in PTH, while another subset responded with normalized urinary calcium excretion. 23 The molecular basis for these differences remains unclear. Studies of families with idiopathic hypercalciuria have revealed genetic loci that may be linked to hypercalciuric nephrolithiasis: chromosome 1q23.3-q24, which contains the human soluble adenylyl cyclase gene; chromosome 12q12-q14, which contains the vitamin D receptor gene; chromosome 9q33.3-q34.2, with candidate gene as yet undetermined.…”
Section: Increased Calcium Excretionmentioning
confidence: 99%
“…22 Recent trials have focused on differentiating subtypes of idiopathic hypercalciuria using prolonged dietary calcium restriction (300 mg/24 h for 3 weeks, 700-1000 mg/24 h for 4 weeks); this revealed that one subset of subjects responded to a low-calcium diet with increasing urinary calcium loss and compensatory rise in PTH, while another subset responded with normalized urinary calcium excretion. 23 The molecular basis for these differences remains unclear. Studies of families with idiopathic hypercalciuria have revealed genetic loci that may be linked to hypercalciuric nephrolithiasis: chromosome 1q23.3-q24, which contains the human soluble adenylyl cyclase gene; chromosome 12q12-q14, which contains the vitamin D receptor gene; chromosome 9q33.3-q34.2, with candidate gene as yet undetermined.…”
Section: Increased Calcium Excretionmentioning
confidence: 99%